Mídia e questão agrária em Minas Gerais: 2005 a 2018 - Victor, Fabiana Borges (2021)
This work objective to understand the elements and meanings represented by the media about the agrarian question, which consequently have an impact on the public opinion formation and in the meanings reproduction about the agrarian and the struggle for land in Minas Gerais. Therefore, we used the news published by the online media, observing the media influence in the narratives construction and an image of this reality in the field, and under which arguments is promoted. It is also our objective to understand the alternatives of socio-territorial movements and subjects that resist on land and in territories, and promoting a counter-discourse in confronting the hegemonic discourse. Therefore, the state of Minas Gerais is considered in the national and international agribusiness scenario, which reflects on the expressive economic activity valorization, correlated to the role of the State. For the development of this analysis, we used reports from the Database the Struggle for Land - DATALUTA, a research project based on the organization, publication and discussion of data related to the agrarian question in Brazil and Minas Gerais, based on the collection of information in print and online newspapers of national, regional or local circulation. The time frame refers to the period 2005-2018, which corresponds to the most recent DATALUTA MG report publication. The discussion of the theme is anchored in two leading perspectives, Geography and Communication, based on concepts such as space and territory, discourse and power, popular and alternative communication, hegemonic and counter-hegemonic communication. We also consider that every communication process represents interests and is related to power relations, revealing the transformations that communication is capable of producing in society, certain that the communication is also ideological. The reports analysis demonstrates a criminalize tendency of socio-territorial movements and their practices, especially with regard to land occupations and the public spaces manifestations. There is also less coverage by the mainstream media of news referring to other themes linked to the agrarian question, such as the healthy foods production and the nature preservation, which in turn are widely publicized by the communication vehicles of the socio-territorial movements themselves. In addition, we also identified a discursive construction and a positive image of agribusiness, mediated by the hegemonic media, in order to emphasize the economic potential and the benefits it can generate for the country.